An Evaluation of the Factors Affection the Potential for Biomass Upgrading for Energy Use in Malaysia - Adam A.A.; Hayder G. (Springer Nature, 2024)
Malaysias rapid urbanization and economic development along with extensive growth in population led to increased energy demand. With the emerging environmental concerns, looking for viable alternatives to secure the energy demand and mitigate the greenhouse gas emissions simultaneously conveyed the attentions toward biogas utilization and extraction from different organic wastes. The concept of waste to wealth is crucial in dealing with various harmful wastes when being dumped instantly to Malaysia landfills, those such as effluent derived from palm oil mills, garden wastes, sewage sludge, food waste, animal manure, and landfill. Thus, either mitigation of threats or valorization of the wastes via biogas generation can be achieved through intensive utilization of anaerobic digestion. For instance, each day in the country 15,000 tons of food is wasted, if treated and utilized properly has the potential to fulfill the energy demanded as it is considered to be 10 times the early consumption, adding to the environmental positive impacts. Therefore, introduction of new polices that promote and encourage the utilization of renewable energy technologies along with adaptation of newly emerging enhancements, are of the Malaysian governments target to reduce the over dependency on the depleted resources. Thus, it is necessary to incorporate significant factors affecting biogas generation for the purpose of energy generation in the country. The current paper assesses the existing biomass treatment technologies based on their effectiveness, evaluates the feedstocks for the purpose of anaerobic digestion based on their organic contents and economic analysis, reviews the biogas to biomethane technologies (evaluation based on economic analysis), and lists most important policies that qualify the incorporation of renewable energy technologies for energy mix targets. Results show that palm oil mill effluent and food wastes have highest potential to produce biogas compared to other feedstocks where co-digestion is preferable for more desired results, additionally, the economic analysis depicts that the palm oil mill effluent still the most favorable followed by the food wastes in term of short payback period, high internal rate of return, and high net present value. 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.